Panorama das atividades de extensão do departamento de engenharia de materiais da UFSCar e oportunidades para sua curricularização na graduação - Almeida, Guilherme Bergaro Sagula de (2023)
Guidelines for service-learning’s curricular use in graduation ensures 10% of the total student workload of undergraduate courses to service-learning activity. This policy has potential to offer benefits in mutual experience, through curriculum connected to reality, which is featured in the new national curriculum guideline. This study analyzed service learning’s activities from the department of materials engineering (DEMa) at UFSCar and opportunities for its curricular use in graduation. Both quantitatively, regarding the existing projects and activities, and qualitatively, debating conditions to service-learning’s curricular use. The methodology used was document and literature’s review to, as result of the first, verify service-learning’s documents, while the second was used to substantiate the debate. 9 programs associated to DEMa and 25 activities, carried out simultaneously with this study, were evaluated. A flowchart was created to demonstrate the feedback relationship between DEMa, materials engineering course and service-learning, reasoned by the principle of inseparability between teaching, researching and service-learning. In addition, other programs that are not directly associated with DEMa, such as junior enterprise and baja team, were evidenced. Thereby, knowing the whole service-learning’s panorama, their relationship with the course pedagogical project (PPC) was understood. Servicelearning’s curricular use is idealized in existing structure’s comprehension, evaluation of different contacts available to the student and institutionalist organization of PPS’s relations. DEMa has a vast and already established service-learning’s structure. Direct participation in this ecosystem is already planned and counted as complementary hours. Indirect ones, mainly real examples in teaching, are likely to institutional organization. Curricular use at DEMa, therefore, is a matter of formalizing the already existing service-learning’s structure.